2018
DOI: 10.3389/fimmu.2018.01727
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals of Factor H and Factor H-Related Proteins in Healthy Children

Abstract: Complement is activated as part of the innate immune defense against invading pathogens. Also, it helps to remove apoptotic debris and immune complexes from the circulation. Impaired complement function due to aberrant plasma levels of complement proteins may be indicative for complement-mediated diseases or can be involved in susceptibility for infections. To determine whether plasma levels are abnormal, reference intervals (RIs) are used from adult healthy donors. Since many complement-mediated diseases have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Previous studies did not find significant differences between sexes in factor H levels in adults ( 57 ). In addition, very recent work did not observe an effect of sex or age in factor H levels in children ( 54 ). However, since we observed a lower AP functional activity in females, a possible explanation for this difference could be higher levels of factor H and/or factor I.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies did not find significant differences between sexes in factor H levels in adults ( 57 ). In addition, very recent work did not observe an effect of sex or age in factor H levels in children ( 54 ). However, since we observed a lower AP functional activity in females, a possible explanation for this difference could be higher levels of factor H and/or factor I.…”
Section: Discussionmentioning
confidence: 86%
“…Troldborg et al studied complement proteins restricted to the lectin pathway and showed comparable results to ours, showing that female have lower complement levels than males ( 53 ). Previously, an animal study demonstrated the influence of sex hormones on the complement system by injecting estrogen and testosterone in healthy and castrated mice from both sexes ( 54 ). Mice treated with testosterone showed increased late acting complement activity while mice treated with estrogen showed diminished activity ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Irmscher et al, 2019, Zhang et al, 2017. A FHR-1 concentration of 11.2 µg/ml was measured in children with two copies of CFHR1; this level was independent of age and gender (Van Beek et al, 2018).…”
Section: Deletion Of Cfhr1 Protection and Riskmentioning
confidence: 99%
“…Early studies investigating FHRs focused on the most abundant FHR, i.e., FHR-1, which was reported to circulate at approximately 40–100 µg/ml in human plasma ( 15 , 17 ). A recent study utilizing a panel of tailor-made detection antibodies reported a lower FHR-1 plasma concentration of approximately 10–15 µg/ml (351 nM) ( 18 ). Two FHR-1 molecular weight variants exist, which both comprise five CCP domains but differ in their number of N-linked carbohydrates (one versus two sites, yielding a 37 or 42 kDa plasma protein, respectively) [reviewed in ( 19 )].…”
Section: Introductionmentioning
confidence: 99%